The Value of Professional Qualities in the Target Model of the Educational Process of Military Training - Рижиков, В. (Київський національний університет імені Тараса Шевченка, 2017)
The article deals with a problem of professional training of future military personnel. The author shows the necessity of developing professional knowledge, skills and abilities, as well as courage, ability to fulfill orders, discipline, self-control and dedication, which are regarded as an obligatory component of the professional training in higher military educational institutions. The effectiveness of professional activities of military personnel is determined by a system of socio-psychological, technical, medical and biological, as well as special military skills.

У процесі професійної підготовки майбутніх військовослужбовців необхідно формувати крім професійних знань, навичок та вмінь також професійні якості до яких ми відносимо: мужність, уміння чітко виконувати накази, дисциплі- нованість, витримка та самовладання, відданість справі, які повинні бути обов'язковою складовою цільової моделі професійної підготовки у вищих військових навчальних закладах. Ефективність професійної діяльності військовослу- жбовців визначається системою соціально-психологічних, технічних, медико-біологічних, а також специфічних профе- сійних якостей військового.
Значення професійних якостей в цільовій моделі навчально-виховного процесу підготовки військових
Keywords: Професійні якості; професійна підготовка військовослужбовців; військова освіта.; Professional qualities; professional training of military personnel; military education.